Sera total oxidant/antioxidant status in lung cancer patients. Issue 37 (September 2019) - Xiang, Miao; Feng, Jiafu; Geng, Lidan; Yang, Yuwei; Dai, Chunmei; Li, Jie; Liao, Yao; Wang, Dong; Du, Xiao-Bo
Abstract : Abstract: We investigated oxidative stress parameters in the sera of patients with lung cancer and healthy individuals to evaluate their correlations with lung cancer. Ninety-four lung cancer patients and 64 healthy controls were enrolled after obtaining informed consent. Their sera oxidative stress parameters were measured. Total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) were significantly different between patients and healthy groups (all P < .001). TAS gradually decreased and TOS and OSI gradually increased from stage I to III, but it did not reach statistical significance (all P > .05). TAS and OSI were significantly different between the nonsmoking and smoking groups, radiotherapy and without radiotherapy groups, chemotherapy and without chemotherapy groups ( P < .05), but not TOS ( P > .05). In a receiver operating characteristic curve analysis comparing patients with lung cancer with healthy controls, the Youden indices of TOS, TAS, and OSI were 0.541, 0.532, and 1, respectively. The oxidative stress may be correlation with lung cancer staging. Smoking, surgery, radiotherapy, and chemotherapy showed correlation with parts oxidative stress parameters.